The Need for Antiviral Drugs for Pandemic Coronaviruses From a Global Health Perspective - Villamagna, Angela Holly; Gore, Sara J.; Lewis, James S.; Doggett, J. Stone (Frontiers in Medicine, 2020)
Respiratory failure due to SARS-CoV-2 has caused widespread mortality, creating an urgent need for effective treatments and a long-term need for antivirals for future emergent coronaviruses. Pharmacotherapy for respiratory viruses has largely been unsuccessful with the exception of early treatment of influenza viruses, which shortens symptom duration and prevents infection in close contacts. Under the rapidly evolving circumstances of the COVID-19 pandemic, most clinical trials of experimental treatments in the United States have focused on later stages of the disease process. Worldwide, the clinical studies of the most impactful drugs, remdesivir and dexamethasone in ACTT-1, RECOVERY and Solidarity, have studied hospitalized patients. Less than half of clinical trials in the U.S. have investigated oral agents, and the majority have taken place in hospitals at a disease stage where the viral load is already decreasing. The limited success of treatments for respiratory viruses and the viral dynamics of COVID-19 suggest that an antiviral therapy with the greatest impact against pandemic coronaviruses would be orally administered, well-tolerated, target a highly conserved viral protein or host-coronavirus interaction and could be used effectively throughout the world, including resource-poor settings. We examine the treatment of respiratory viral infections and current clinical trials for COVID-19 to provide a framework for effective antiviral therapy and prevention of future emergent coronaviruses and call attention to the need for continued preclinical drug discovery.